Severe and fatal mass attacks by 'killer' bees (Africanized honey bees--Apis mellifera scutellata) in Brazil: clinicopathological studies with measurement of serum venom concentrations. - França, F; Benvenuti, L; Fan, H; Santos, D; Hain, S; Picchi-Martins, F; Cardoso, J; Kamiguti, A; Theakston, R; Warrell, D (1994)
In São Paulo State, Brazil, five males, aged between 8 and 64 years, were attacked by 'Africanized' honey bees (Apis mellifera scutellata). The estimated number of stings received by each patient ranged from > 200 to > 1000. All five were transferred to intensive care units in São Paulo City. Clinical features included intravascular haemolysis, respiratory distress with ARDS, hepatic dysfunction, rhabdomyolysis (with myoglobinaemia and myoglobinuria), hypertension and myocardial damage (perhaps explained by release of endogenous catecholamines by venom phospholipase A2 and mellitin), shock, coma, acute renal failure and bleeding. Laboratory findings included gross neutrophil leucocytosis, elevated serum enzymes [AST, ALT, LDH, CPK (predominantly CPK-MM)] and creatinine. Clotting times were slightly prolonged. Despite treatment with antihistamines, corticosteroids, bronchodilators, vasodilators, bicarbonate, mannitol and mechanical ventilation, three of the patients died between 22 and 71 h after the attacks, with histopathological features of ARDS, hepatocellular necrosis, acute tubular necrosis, focal subendocardial necrosis and disseminated intravascular coagulation. Whole bee venom and phospholipase A2 (PLA2) antigen concentrations were measured in serum and urine for the first time, using enzyme immunoassay. High venom and PLA2 concentrations were detected in serum and urine for more than 50 h after the stings in two fatal cases, in one of which the total circulating unbound whole venom was estimated at 27 mg, one hour after the attack. An antivenom should be developed to treat the increasing numbers of victims of mass attacks by Africanized 'killer' bees in USA, Middle and South America.